Cyclic performance of geosynthetic-encased granular pile with tire chips and aggregates mixture in soft soil – A model study - Muni Pradeep N.; Kumar S. (My University, 2025)
The performance of encased granular piles subjected to heavy cyclic loading presents a significant concern in the current context. Meanwhile, global waste tire management poses a major challenge because it has a detrimental effect on the environment. To address both difficulties, this research utilizes recycled tire chips derived from end-of-life tires (ELTs) and substituting traditional aggregates in granular pile construction. This study summarizes laboratory model tests investigating the performance of geosynthetic encased granular piles designed for soft soil improvement under vertical cyclic loading. The composition of the granular pile comprised (25 % tire chips + 75 % aggregates). Various cyclic loading parameters were scrutinized, including the selection of encasement material and the best configuration for granular piles, cyclic loading frequency (f), cyclic loading amplitude (qca), length-to-diameter (L/D) ratios, granular pile end conditions, and strength of surrounding soft soil. The novel feature of this research is the evaluation of the cyclic induced settlement (Sc) – excess pore water pressure (Pexc) coupled performance for all considered factors and its effects on the encased granular piles improved soft ground under vertical cyclic loading. Key findings include ordinary granular piles (OGP) illustrated optimal performance when subjected to lower frequency and amplitude loading, smaller L/D ratios, and end bearing conditions. The provision of Combi-grid encasement notably improved the cyclic performance of granular piles by substantially reducing the cyclic induced settlement (Sc) on improved soft beds across all examined factors. This research also discusses the increased cyclic stress on the surrounding soft soil initiated excess pore water pressure (Pexc) development and is reduced to a greater extent with the help of Combi-grid encasement across all test cases. © 2024 Elsevier Ltd